Game Changer: The Influence of Circuit Training on Motor Skills among Football Players - Sakthivel, S.; Rangaraj, K. (Journal of Neonatal Surgery, 2025)
Motor skills are essential for football players as they directly impact a player’s performance and ability to execute critical movements with precision and speed. Consistent practice and training help develop these skills, which include hand-eye coordination, footwork, and spatial awareness. Examining how circuit training affected particular motor fitness components in male collegiate football players at SRM Institute of Science and Technology in Kattankulathur, Tamil Nadu, India, was the goal of the study. Fifteen male football players, ranging in age from 17 to 23, were chosen at random to participate. The study used a single-group design and included assessments before and after the test. The experimental group underwent circuit training, and initial tests were conducted on all participants to evaluate selected motor fitness parameters. Following a 12-week training period, post-tests were administered, and the results were recorded. The motor fitness variables assessed included speed, endurance, flexibility, and agility. Data from the pre- and post-tests were analyzed using mean, standard deviation, and paired samples t-test, with a confidence level set at 0.05 due to the limited sample size. The findings revealed that circuit training significantly improved motor fitness variables in the male football players at SRM Institute of Science and Technology.